Biological invasions, ecological resilience and adaptive governance. (1st December 2016) - Chaffin, Brian C.; Garmestani, Ahjond S.; Angeler, David G.; Herrmann, Dustin L.; Stow, Craig A.; Nyström, Magnus; Sendzimir, Jan; Hopton, Matthew E.; Kolasa, Jurek; Allen, Craig R.
Abstract: In a world of increasing interconnections in global trade as well as rapid change in climate and land cover, the accelerating introduction and spread of invasive species is a critical concern due to associated negative social and ecological impacts, both real and perceived. Much of the societal response to invasive species to date has been associated with negative economic consequences of invasions. This response has shaped a war-like approach to addressing invasions, one with an agenda of eradications and intense ecological restoration efforts towards prior or more desirable ecological regimes. This trajectory often ignores the concept of ecological resilience and associated approaches of resilience-based governance. We argue that the relationship between ecological resilience and invasive species has been understudied to the detriment of attempts to govern invasions, and that most management actions fail, primarily because they do not incorporate adaptive, learning-based approaches. Invasive species can decrease resilience by reducing the biodiversity that underpins ecological functions and processes, making ecosystems more prone to regime shifts. However, invasions do not always result in a shift to an alternative regime; invasions can also increase resilience by introducing novelty, replacing lost ecological functions or adding redundancy that strengthens already existing structures and processes in an ecosystem. This paper examines the potential impacts of species invasions on the resilience of ecosystems and suggests that resilience-based approaches can inform policy by linking the governance of biological invasions to the negotiation of tradeoffs between ecosystem services. Highlights: The relationship between biological invasions and ecological resilience is complex. Invasions can build or erode resilience, which can be positive or negative. Invasions have great capacity to affect global environmental change. Biological invasions affect ecological resilience and ecosystem services. Adaptive governance approaches biological invasions as suites of ecosystem services.